The effect of a perceptual-motor training programme on the coincident anticipation timing and batting performance of club cricket players - van Velden, G. D. (University Stellenbosch, 2010)
The purpose of this study was to determine the effects of a perceptual-motor training programme on the coincident anticipation timing and batting performance of university club cricket players. The intervention programme focused on developing players. visual attention and concentration. Vickers. (2007) Three-Step Decision Training Model was used to structure the training sessions. The study followed a repeated measures experimental design with three groups (experimental, placebo, and control) formed by volunteers from a university club cricket team. The independent variable was a four-week training programme. The dependent variables were coincident anticipation timing and performance on a cricket batting test. Subjects were pre- and post-tested with retention tests occurring after a set period of ¡°no training¡± following the post-tests. Differences between groups were compared using Kruskal-Wallis ANOVA by Ranks Tests. Differences within each group were compared using multiple Mann-Whitney U-Tests. No significant improvements were observed in the experimental group.s coincident anticipation timing and batting performance. Although neither coincident anticipation timing nor batting performance significantly improved, further research into the use of Vickers. (2007) Model to enhance sport performance is recommended.